Surface characteristics of wood polypropylene nanocomposites reinforced with multi-walled carbon nanotubes - Kaymakçı, Alperen; Birinci, Emre; Ayrılmış, Nadir (Elsevier BV, 2019)
Abstract Effect of multi-walled carbon nanotubes (MWCNT) content on the surface roughness, wettability, and scratch hardness properties of wood/polypropylene nanocomposites were investigated. To meet this objective, pine wood flour, polypropylene with and without coupling agent (maleic anhydride grafted polypropylene), and multi-walled carbon nanotube (0, 1, 3 or 5 wt%) were compounded in a twin screw co-rotating extruder. The mass ratio of the pine wood flour to polypropylene was 50/50 (w/w) in all the composite formulations. Test samples were manufactured using injection molding machine from the pellets. The surface roughness, wettability, and scratch hardness properties of the wood/polypropylene nanocomposites reinforced with multi-walled carbon nanotubes were determined. The surface roughness values of the nanocomposite specimens decreased with increasing MWCNT content. The MWCNT reinforced wood/polypropylene nanocomposites without coupling agent had higher surface roughness values than the ones with coupling agent. The wettability of the nanocomposite specimens decreased with increasing content of the MWCNT. The incorporation of the coupling agent into the wood/polypropylene nanocomposites decreased the wettability of the specimens. The scratch hardness values of the nanocomposite specimens improved with increasing MWCNT content.
Keywords: Surface roughness; MWCNT; Wettability; Polypropylene; Wood; Nanocomposites